Strategic immunization and group structure - Andrea Galeotti; Brian W. Rogers (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2012)
We consider the spread of a harmful state through a population divided into two groups. Interaction patterns capture the full spectrum of assortativity possibilities. We show that a central planner who aims for eradication optimally either divides equally the resources across groups, or concentrates entirely on one group, depending on whether there is positive or negative assortativity, respectively. We study a game in which agents can, at a cost, immunize. Negative assortative interactions generate highly asymmetric equilibrium outcomes between ex-ante identical groups. When groups have an underlying difference, even a small amount of inter-group contacts generates large asymmetries.
Keywords: 330